Anti-inflammatory Effect of Apigenin Obtained by Portulaca oleracea L in ‎Male Mice - K. Fahd, Ahmed; Saliem, Ali (The Iraqi Journal of Veterinary Medicine, 2024)
This study aimed to evaluate the potential anti-inflammatory effects of ‎‎apigenin, obtained from Portulaca oleracea L., using a male mouse model‎. A total of 56 ‎healthy BLAB/c albino male mice (Mus musculus) were used in two experiments. In the first experiment‎, ‎the xylene-induced ear edema, 28 male mice were randomly divided into four groups (n=7). ‎The negative control group received distilled water, while the positive control, apigenin-‎treated, and indomethacin-treated groups were exposed to xylene (0.03 mL applied to ‎the anterior and posterior surface of the right ear lobe) to induce inflammation. ‎Subsequently, the apigenin-treated group received orally 50 mg/kg BW apigenin, and ‎the indomethacin-treated group received orally 0.36 mg/kg BW indomethacin.‎ Ear weight ‎difference was calculated as an indicator ‎of anti-inflammatory. For the second experiment, the carrageenan-induced paw edema‎, a ‎similar experimental design was followed, but carrageenan (50 ‎mg/kg BW of 1% solution) ‎was ‎administered intra-dermally‎ in the right hindpaws.‎ Paw skin thickness difference ‎and differential white blood ‎cells (WBCs) count, along with the ‎quantification of prostaglandin E-2 ‎‎(PGE-2) and ‎interleukin-6 (IL-6) in serum samples, were used as indicators of anti-inflammatory.‎ Results showed that xylene exposure led ‎to a significant ear weight increase, ‎indicative of ‎inflammation. Conversely, the ‎apigenin-treated group demonstrated a ‎reduction in ear ‎weight compared to the positive control group. Similarly, carrageenan ‎administration resulted ‎in a substantial ‎increase in paw skin thickness and elevated levels of ‎WBCs count, PGE-2, ‎and IL-6. ‎Apigenin treatment significantly mitigated these ‎inflammatory markers, ‎‎outperforming indomethacin in PGE-2 ‎and IL-6‎. This study provides evidence supporting the potential ‎of P. oleracea-derived ‎apigenin as an effective anti-inflammatory agent, showing ‎comparable or better ‎efficacy ‎than indomethacin‎‎‎‎‎.